Clinical outcome and outcome prediction of octogenarians with acute basilar artery occlusion and endovascular stroke treatment compared to younger patients - Weyland, Charlotte Sabine; Mutke, Matthias Anthony; Zimmermann-Miotk, Amanda; Schmitt, Niclas; Chen, Min; Schönenberger, Silvia; Möhlenbruch, Markus; Bendszus, Martin; Jesser, Jessica (Frontiers in Neurology, 2023)
Octogenarians, are underrepresented in recently published studies, that showed a benefit of endovascular stroke treatment (EST) for patients with acute basilar artery occlusion (BAO). We aimed to compare the clinical outcome of octogenarians with BAO and EST compared to younger patients (YP) and to identify independent outcome predictors.This is a retrospective, single-center analysis of patients treated for BAO with EST from 01/2013 until 06/2021 in a tertiary stroke center. Octogenarians (80-89 years) were compared to YP. Study endpoint was favorable clinical outcome as per mRS 0-3 90 days after stroke onset. The study groups were compared in univariate analysis and a multivariable logistic regression analysis was performed to define independent predictors for favorable and unfavorable (mRS 5-6) clinical outcome.In this study cohort, 74/191 (38.7%) octogenarians had a higher pre-stroke mRS (Median, IQR: 2, 1 -3 octogenarians vs. 0, 0 -1 YP, p < 0.001) and a comparable NIHSS before EST (Median, IQR: 21, p = 0.487). They showed a comparable rate of favorable outcome (mRS 0-3 90d, 23.0 % vs. 25.6 % in YP, p = 0.725), but were less often functionally independent (mRS 0-2: 10.8% in octogenarians vs. 23.0% in YP, p = 0.049). The rate of unfavorable clinical outcome was comparable (mRS 5-6, n = 40, 54.1% in octogenarians vs. n = 64, 54.7% in YP, p = 0.831). Baseline NIHSS was an independent predictor for clinical outcome in YP (e.g. for unfavorable clinical outcome: OR 1.061, CI 1.027-1.098, p = 0.005) and for favorable clinical outcome in octogenarians. Pre-stroke mRS predicted favorable outcome in octogenarians (OR 0.54, CI 0.30 -0.90, p = 0.0291) while age predicted unfavorable outcome in YP (OR 1.045, CI 1.011 -1.086, p = 0.0137).Octogenarians with acute BAO eligible for EST are as likely to achieve favorable outcome as YP and the rate of death or severe disability is comparable. The admission NIHSS is an independent predictor for favorable and unfavorable outcome in YP and for favorable outcome in octogenarians. In this study cohort, pre-stroke mRS predicted favorable outcome in octogenarians while age predicted unfavorable outcome in YP.